Modern Concepts of Management Toolbox for Market’s Pioneers and Operators - Krystian Pawlowski (Communications of International Proceedings, 2020)
In the literature related to strategic analysis and strategic choices, we find a very broad discussion on the interaction between an enterprise and its environment, situational selection of the enterprise's strategy depending on the conditions of its environment. The operational expression of the adopted strategies are concepts, methods and techniques of business management. On the other hand, internal conditions affect the scope and results of implementing management methods both on the side of barriers and factors favouring implementation. The following paper, out of many internal factors shaping the situational selection of modern management methods, assumes that leading ones are: standard (SSD) or non-standard (NSD) mode of operation related to the level of enterprise’s innovation. A group of 150 medium and large enterprises of the industry in Poland were examined as a part of the research. The goal of the study was to identify the modern management methods which are used and their correlation with achieved economic results. The practical implications of the work results is the development of modern concepts of management toolboxes for Pioneers and Market Operators.
Keywords: Innovation; Modern Concepts of Management Toolboxes; Market Pioneers; Market Operators.